Intestinal intraepithelial lymphocyte activation promotes innate antiviral resistance - Swamy, Mahima; Abeler-Dörner, Lucie; Chettle, James; Mahlakõiv, Tanel; Goubau, Delphine; Chakravarty, Probir; Ramsay, George; Reis e Sousa, Caetano; Staeheli, Peter; Blacklaws, Barbara A.; Heeney, Jonathan L.; Hayday, Adrian C. (Nature communications, 2015)
Unrelenting environmental challenges to the gut epithelium place particular demands on the local immune system. In this context, intestinal intraepithelial lymphocytes (IEL) compose a large, highly conserved T cell compartment, hypothesized to provide a first line of defence via cytolysis of dysregulated intestinal epithelial cells (IEC) and cytokine-mediated re-growth of healthy IEC. Here we show that one of the most conspicuous impacts of activated IEL on IEC is the functional upregulation of antiviral interferon (IFN)-responsive genes, mediated by the collective actions of IFNs with other cytokines. Indeed, IEL activation in vivo rapidly provoked type I/III IFN receptor-dependent upregulation of IFN-responsive genes in the villus epithelium. Consistent with this, activated IEL mediators protected cells against virus infection in vitro , and pre-activation of IEL in vivo profoundly limited norovirus infection. Hence, intraepithelial T cell activation offers an overt means to promote the innate antiviral potential of the intestinal epithelium. Intraepithelial lymphocytes in the gut eliminate dysfunctional epithelial cells and promote regrowth of healthy cells. Here the authors show that, in addition, these lymphocytes protect cells against viral infections by rapidly activating interferon-dependent pathways in intestinal epithelial cells.